Prevalence of Daytime Urinary Incontinence and Related Risk Factors in Primary School Children in Turkey - Bolat, Deniz; Acar, Ismail Cenk; Zumrutbas, Ali Ersin; Eskicorapci, Saadettin; Sancak, Eyup Burak; Zencir, Mehmet; Turan, Tahir; Sinik, Zafer (KOREAN UROLOGICAL ASSOC, 2014)
Purpose: Urinary incontinence is one of the major urinary symptoms in children and adolescents and can lead to major distress for the affected children and their parents. In accordance with the definitions of the Standardization Committee of the International Children's Continence Society, daytime urinary incontinence (DUI) is uncontrollable leakage of urine during the day. The aim of this cross-sectional study was to investigate the prevalence and associated risk factors of DUI in Turkish primary school children. Materials and Methods: The questionnaire, which covered sociodemographic variables and the voiding habits of the children, was completed by the parents of 2,353 children who were attending primary school in Denizli, a developing city of Turkey. The children's voiding habits were evaluated by use of the Dysfunctional Voiding and Incontinence Symptoms Score, which is a validated questionnaire. Children with a history of neurological or urological diseases were excluded. Results: The participation rate was 91.9\% (2,164 people). The overall prevalence of DUI was 8.0\%. The incidence of DUI tended to decrease with increasing age and was not significantly different between genders (boys, 8.8\%

girls, 7.3\%

p=0.062). Age, maternal education level, family history of daytime wetting, settlement (urban/rural), history of constipation, urinary tract infection, and urgency were independent risk factors of DUI. Conclusions: Our findings showed that DUI is a common health problem in primary school children. In an effort to increase awareness of children's voiding problems and the risk factors for urinary dysfunction in the population, educational programs and larger school-based screening should be carried out, especially in regions with low socioeconomic status.
Keywords: Child; Diurnal enuresis; Prevalence; Risk factors; Urination disorders